Age determination of the wildcat (Felis silvestris): a case study of a sample from the North-Western Black Sea region (Ukraine) - Yuri Oleinik (Theriologia Ukrainica)
In recent decades, the wildcat (Felis silvestris) population has been increasing along the eastern edge of its range in Ukraine, associated with the recolonisation of territories previously inhabited by the species. An essential aspect of analysing this process is studying population dynamics, including sex and age structures. Knowing the individual age of animals is a crucial prerequisite for investigating many aspects of their life cycle and population dynamics. This information is particularly important for Felis silvestris, a rare species included in international and national lists of protected animals, for the conservation and management of its populations. This necessitates the verification of age determination methods in specific Felis silvestris populations, particularly in the south-western regions of Ukraine. To determine the age of wildcats, we employed both traditional, non-invasive methods—such as analysing suture obliteration and dental morphometric characters—and methods requiring partial tooth destruction, such as studying changes in dentin volume and cementum in the root of the canines. Cementochronology was found to be the only method allowing the wildcat population to be divided into seven year classes. Cement deposition primarily occurs at the apical tip of the canine root, allowing the use of only the lower third of the tooth for analysis. This is particularly important when working with collection materials of rare species. In the first year of life (0+), dentin fills no more than 20% of the pulp cavity width. In subsequent year classes, dentin deposition occupies at least 70% of the pulp cavity volume, enabling a clear division of the wildcat population into two groups: young (0+) and older individuals. The distance between the enamel at the neck of the canine and the edge of its alveolus is an effective tool for distinguishing young and adult individuals. The analysis of alveolar recession relative to the neck enamel can be considered a promising method for determining age groups in wildcats, including both deceased and living individuals. The use of basicranial sutures of the skull was found to be less informative: the sutures at the skull base ossify late, while the obliteration between the maxilla and premaxilla in the nasal area is only partially expressed.